2021
DOI: 10.1002/tcr.202000165
|View full text |Cite
|
Sign up to set email alerts
|

How and Why to Investigate Multicomponent Reactions Mechanisms? A Critical Review

Abstract: We review the most innovative efforts and greatest challenges faced when elucidating multicomponent reactions (MCRs) mechanisms. When compared to traditional reactions, the often two or more concurrent reactions pathways and the greater number of possible intermediates in MCRs turn their mechanistic investigation both a harder and trickier task. The common approaches used to investigate reaction mechanisms are often unable to clarify MCRs mechanisms; hence few but clever approaches are currently used to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 106 publications
0
29
0
Order By: Relevance
“…We also proposed a plausible reaction mechanism for the asymmetric Biginelli reaction. Recently, a review has been published on the mechanism of multicomponent reaction which comprises all the possible reaction pathways [22] . Feng also reported that prolinamide catalyzed asymmetric Biginelli reaction by a dual activation route [17] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also proposed a plausible reaction mechanism for the asymmetric Biginelli reaction. Recently, a review has been published on the mechanism of multicomponent reaction which comprises all the possible reaction pathways [22] . Feng also reported that prolinamide catalyzed asymmetric Biginelli reaction by a dual activation route [17] .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a review has been published on the mechanism of multicomponent reaction which comprises all the possible reaction pathways. [22] Feng also reported that prolinamide catalyzed asymmetric Biginelli reaction by a dual activation route. [17] The CIL 3 b was treated with p-TSA and 1 H-NMR spectrum of the salt of CIL 3 b.p-TSA (I) show the À CONH and À OCH protons of prolinamide are interacting through hydrogen bonding with p-TSA anion, which shifted the 1 H-NMR spectral peaks downfield (7.43 to 7.96 δ ppm of proline À CONH, and 5.07 to 5.26 δ ppm of À OCH) (SI, Figure S1).…”
Section: Scope and Limitations Of The Cil 3 B Catalyzed Biginelli Reactionmentioning
confidence: 99%
“…Multicomponent reactions (MCRs), which employ three or more reactants to yield a product derived from all the starting materials in a one-pot manner, have long been recognized as a powerful tool to enrich molecular diversity in natural product synthesis and medicinal chemistry [ 33 , 34 , 35 ]. However, the revelation of the reaction mechanisms of MCRs, which is crucial for condition optimization and the manipulation of stereochemistry outcomes, has always been a challenging task due to the multiple potential reaction pathways and the difficulty of capturing key intermediates [ 35 , 36 , 37 ]. To elucidate the reaction pathway for the three-component synthesis of β-carbamate ketones, we separately tested the reactivity of each component to another under solvent-free conditions.…”
Section: Resultsmentioning
confidence: 99%
“…MCR mechanism studies pose a huge challenge, as we have highlighted elsewhere [ 29 ]. MCRs typically have two or more mechanistic pathways (see a pictorial view in Scheme 2 ); hence, the possibility of concurrent but usually concomitant reaction pathways makes the investigation of such transformations a tricky and laborious task.…”
Section: Mechanistic Considerations Of Mcrs and Catalysis Rolesmentioning
confidence: 99%